85 Prediction of response to biventricular pacing from dyssynchrony indices: the absolute limit on predictability, and its clinical implications. (9th June 2011) - Nijjer, S S; Pabari, P; Stegemann, B; Palmieri, V; Freemantle, N; Hughes, A; Francis, D P
Abstract : Background: It may be incorrect to believe that, with a good echocardiographic marker of mechanical dyssynchrony, response to biventricular pacing (BVP) should be predictable with a high r 2 value. Variability between repeat echocardiographic measurements, and between successive dyssynchrony measurements, may reduce r 2 . Both will mandatorily limit the achievable r 2 ; we determine this "contraction factor". Method and Results: We compared correlation coefficients of dyssynchrony indices with response markers, in externally monitored randomised controlled trials (EMRCTs) and highly skilled single centre studies (HSSCSs). ΔLVEF in CRT recipients comprises true CRT effect plus unpredictable spontaneous variability present in control patients (Abstract 85 figure 1, upper panel). The resultant depression in r 2 is calculated. HSSCSs overstate r 2 between dyssynchrony and remodelling response in contrast to EMRCTs (p<0.0000000001), whether response is LVEF (0.40 vs 0.01), ESV (0.26 vs 0.01); EDV (0.53 v 0.01). An "averaged" reported r 2 between differing dyssynchrony markers to commonly used echocardiographic response markers is shown in Abstract 85 figure 1, lower panel. EMRCT data shows maximal r 2 between dyssynchrony and ΔLVEF is 0.57 (ΔESV, 0.54; ΔEDV, 0.50). Dyssynchrony indices' own variability further contracts observable r 2 values (by x0.68). The overall ceiling to r 2 is between dyssynchrony and ΔLVEF is 0.39 (ΔESV, 0.37; ΔEDV, 0.34). All EMRCT r 2 values obey these statistical limits; 29% of HSSCSs results do not. Conclusions: HSSCSs suggest dyssynchrony markers strongly predict response to BVP but EMRCTs cannot confirm this. Natural variability forces observed correlation coefficients between dyssynchrony and response to be low. EMRCTs, being less susceptible to publication bias, reflect this reliably. Frequent citation (without verification in independent cohorts) of the most exuberant values, from HSSCSs creates mathematically unviable, unrealistic, expectations. Simply searching for progressively more extreme correlations is therefore misguided. Rationally, we should concentrate on improving test-retest reproducibility of markers of dyssynchrony and of response.